USE OF HADITHS IN CONTRIBUTING NATIONAL VALUES IN YOUNG PEOPLE - Nurmanova, Dilfuzaxon; Ismoilova, Surmaxon; Ismoilova, Surmaxon; Teshaboeva, Gulnozaxon ,; Isroilova, Barchinoy (International Journal of Psychosocial Rehabilitation, 2020)
This paper makes analyses of the use of hadiths in contributing national values in young people. On this way research has been mentioned on different points of the hadiths. Research has been contributing on the national values in young people.